O setor de gás natural na Argentina: privatizações, problemas regulatórios e ação estatal no período Kirchner - Santana, Cilene Cardoso (2010)
The purpose of this paper is to evaluate the process of privatization in Argentina, specifically in the infrastructure sector, with emphasis on the natural gas industry, which accounts for 50% of the country's energy matrix. After exposing the motivations of policies in the 1990s with this objective, there is a discussion of the main consequences of the withdrawal of state control of resources in the energy sector in the Argentine economy, due to the way this process was conducted, and the picture resulting in particular as regards the regulation of the sector. With the new political landscape of the region, from the early years of this decade, returned to debate the desirability of the state to resume more active roles in the energy sector, in addition to regulatory tasks as part of new development proposals in progress. In the case of Argentina, the Kirchner government has sought to establish new forms of action, even without clear results